2016
DOI: 10.1016/s0140-6736(16)30467-6
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of urinary sodium excretion with cardiovascular events in individuals with and without hypertension: a pooled analysis of data from four studies

Abstract: Full funding sources listed at end of paper (see Acknowledgments).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
331
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 413 publications
(353 citation statements)
references
References 61 publications
8
331
0
14
Order By: Relevance
“…For riskoutcome pairs for which no recent systematic review was available, we either updated reviews developed for GBD 2013 or did a new systematic search of literature (methods appendix pp . Table 2 summarises the evidence using multiple dimensions, which supports our assessment that each included risk-outcome pair meets the criteria of convincing or probable evidence (methods appendix [pp [12][13] contains a justifi cation of the criteria presented to support causality). In this summary of evidence, we have focused on randomised controlled trials and prospective observational studies, along with supporting evidence, like dose-response relationships and biologically plausible mechanisms.…”
Section: Causal Evidence For Risk-outcome Pairsmentioning
confidence: 66%
See 3 more Smart Citations
“…For riskoutcome pairs for which no recent systematic review was available, we either updated reviews developed for GBD 2013 or did a new systematic search of literature (methods appendix pp . Table 2 summarises the evidence using multiple dimensions, which supports our assessment that each included risk-outcome pair meets the criteria of convincing or probable evidence (methods appendix [pp [12][13] contains a justifi cation of the criteria presented to support causality). In this summary of evidence, we have focused on randomised controlled trials and prospective observational studies, along with supporting evidence, like dose-response relationships and biologically plausible mechanisms.…”
Section: Causal Evidence For Risk-outcome Pairsmentioning
confidence: 66%
“…76 Although multiple lines of epidemiological evidence support the harmful eff ects of very high levels of sodium intake, no scientifi c consensus has been reached on the optimal level of sodium intake. In GBD 2013, on the basis of fi ndings of the Prospective Urban Rural Epidemiology (PURE) collaboration on sodium and cardiovascular mortality 13,77 and to incorporate the absence of scientifi c consensus on the optimal intake of sodium, we expanded the uncertainty for the TMREL for sodium to 1-5 g per day.…”
Section: Sodium Intakementioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, American Heart Association News reported a study that suggested that reducing excessive salt benefits some people with high blood pressure, but low-sodium diets do not help people with lower risks for heart disease, stroke or death. A study published in the Lancet [6] involved more than 130,000 people from 49 countries, concluded that low-salt diets in people with and without high blood pressure may actually increase the risk of cardiovascular disease and death compared to average salt consumption. Criticism of that study in the Lancet correspondence (Lancet 388, page 2111) only goes to show the persistence of the proponents of the low salt diet and the apparent power they have with governments.…”
mentioning
confidence: 99%